2015
DOI: 10.1152/ajplung.00306.2014
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl mediated tyrosine phosphorylation of paxillin regulates LPS-induced endothelial dysfunction and lung injury

Abstract: Fu P, Usatyuk PV, Lele A, Harijith A, Gregorio CC, Garcia JG, Salgia R, Natarajan V. c-Abl mediated tyrosine phosphorylation of paxillin regulates LPS-induced endothelial dysfunction and lung injury. Am J Physiol Lung Cell Mol Physiol 308: L1025-L1038, 2015. First published March 20, 2015 doi:10.1152/ajplung.00306.2014Paxillin is phosphorylated at multiple residues; however, the role of tyrosine phosphorylation of paxillin in endothelial barrier dysfunction and acute lung injury (ALI) remains unclear. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Our present study did not observe Y907 undergoing phosphorylation in cells exposed to LPS, indicating different tyrosine kinases may be activated under various stimulation conditions that direct PARP1 phosphorylation at different sites. However, both serine and tyrosine phosphorylations are observed in cells upon LPS stimulation (15,54), which opens a question as to how these two modifications cross-talk. The role of nonreceptor tyrosine kinases in PARP1 phosphorylation and activation has not drawn much attention.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study did not observe Y907 undergoing phosphorylation in cells exposed to LPS, indicating different tyrosine kinases may be activated under various stimulation conditions that direct PARP1 phosphorylation at different sites. However, both serine and tyrosine phosphorylations are observed in cells upon LPS stimulation (15,54), which opens a question as to how these two modifications cross-talk. The role of nonreceptor tyrosine kinases in PARP1 phosphorylation and activation has not drawn much attention.…”
Section: Discussionmentioning
confidence: 99%
“…ALI induced by LPS is associated with vascular dysfunction (Fu et al 2015;Griffiths et al 1995). Zhang et al (2010) reported that pulmonary arteries of LPStreated rats have an increase in the contractile response to PE.…”
Section: Activation Of Nf-κb Is Increased During Inflammation and It mentioning
confidence: 99%
“…Acute respiratory distress syndrome (ARDS) is characterized by severe pulmonary inflammation, increased capillary endothelial permeability and a high mortality rate [1,2]. Lipopolysaccharide (LPS), a bacterial endotoxin and potent mediator of endothelial activation, induces proinflammatory cytokines and adhesion molecules, as well as the generation of reactive oxygen species (ROS), oxidative stress, apoptosis, inflammation, pulmonary vascular endothelial cell dysfunction, and pulmonary microvascular permeability [3][4][5]. LPS-induced dysfunction of pulmonary vascular endothelial cells is clinically important as it presents early in the course of ARDS and is associated with higher mortality [6,7].…”
Section: Introductionmentioning
confidence: 99%